Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s13019-018-0733-6
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid surgery in treatment of pulmonary sequestration with abdominal aorta feeding vessel: a case report

Abstract: BackgroundPulmonary sequestration is a rare congenital pulmonary dysplasia, which requires surgical resection (either via open thoracotomy or video-assisted thoracoscopic surgery [VATS] or via endoluminal occlusion of the abnormal feeding vessel).Case presentationWe described a 51-year-old female patient with a history of recurrent cough and repeated pneumonia. She was referred to our hospital for further work-up of pulmonary sequestration. We performed a hybrid surgery (i.e., embolization of the aberrant feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…Thus, in patients who undergo surgery for PS, the appropriate and safe management of an aberrant artery is the most important factor considered by thoracic surgeons. With the development of endovascular techniques, several reports have shown that preoperative coil embolization is effective in decreasing the risk of serious intraoperative hemorrhage [3][4][5][6][7]. However, challenges associated with the procedure, similar to those observed in the current case, have not been discussed in previous studies.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, in patients who undergo surgery for PS, the appropriate and safe management of an aberrant artery is the most important factor considered by thoracic surgeons. With the development of endovascular techniques, several reports have shown that preoperative coil embolization is effective in decreasing the risk of serious intraoperative hemorrhage [3][4][5][6][7]. However, challenges associated with the procedure, similar to those observed in the current case, have not been discussed in previous studies.…”
Section: Discussionmentioning
confidence: 65%
“…However, the optimal management of an aberrant artery is controversial. Several studies have shown that hybrid surgery with preoperative coil embolization for an aberrant artery can effectively reduce the risk of serious intraoperative hemorrhage [3][4][5][6][7]. However, there are no clear indications for the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The arteries feeding the PS have some particularities that pose a challenge for treatment: they carry blood under systemic pressure, in a fragile, thin-walled artery, which can lead to accelerated atherosclerotic changes and is more susceptible to damage from recurrent pulmonary infections or tear injuries. 4 , 6 , 7 In addition, inflammatory changes associated with recurrent PS infections distort the normal anatomy and can make open surgery very difficult.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The potential risks of massive hemorrhage or retraction into the abdomen make it advisable to completely resect the sequestration artery from its abdominal origin, requiring addition of laparotomy, lengthening the duration of surgery, or addition of embolization of its origin prior to pulmonary resection. 6 , 7…”
Section: Discussionmentioning
confidence: 99%
“…Other congenital pulmonary malformations are sometimes associated with PS, possibly increasing the risk of carcinogenesis. In most cases, PS is diagnosed during childhood or adolescence but occasionally diagnosis can be delayed until adult age, when clinical presentation ranges from asymptomatic to, more often, recurrent chest infections and severe haemoptysis 2,3 …”
Section: Figurementioning
confidence: 99%